What accounts for Duverger's law? The behavioral mechanisms underpinning two-party convergence in India. (October 2021) - Ziegfeld, Adam
Abstract: Duverger's Law states the single-member district plurality rules should produce two-party competition. In district-level election races where this expectation holds, what political behaviors—ranging from elites' strategic formation of political parties to voters' strategic abandonment of losing candidates—account for these outcomes? Using data from state elections in India, this article demonstrates that no single mechanism accounts for most electoral outcomes consistent with Duverger's Law. However, mechanisms related to the behavior elites, far more than voters, produce convergence on two-party competition. This article uncovers relatively little evidence of outcomes driven by strategic voting, instead finding that much of the convergence on two parties is attributable to various forms of strategic entry in which parties selectively field candidates in certain races. In particular, elite collusion—when multiple parties coordinate on where to field candidates—is especially important. Data from other countries confirm that these findings are not unique to India.